The Role of Top Management Support and Technological Competencies in the Influence of Digital Business Transformation on Organizational Resilience - Nelson, Alden; Utami, Velly Fitri; Indah, Yuli (Bandung: Prodi Manajemen FE Universitas Langlangbuana, 2025)
Abstract: The biggest challenge for SMEs in the market of emerging countries is related to their survival ability. To enable survival, businesses are required to implement digital business transformation as an adaptive step to respond to changes in culture, trends, and markets in the industry. This is accompanied by top management support to foster technological competencies, in proceeding with an increase of organizational resilience. This research aims to analyze the top management support role as well as the technological competence in linking the influence of digital business transformation with organizational resilience. The approach used is a quantitative one, through a collection of questionnaires to 200 respondents who are owners/managers of SME businesses in Batam City. Data analysis through SEM-PLS technique via SmartPLS software. The test results indicate digital business transformation’s effect is significant on top management support and technological competencies, technological competencies have a significant effect on the resilience of the organization. Additionally, digital business transformation also plays a significant direct influence on the resilience of organizations.